DETERMINANTS OF NON-MUSLIM BEHAVIORAL INTENTION TO USE ISLAMIC BANKING SERVICE IN INDONESIA: AN EXTENDED THEORY OF PLANNED BEHAVIOR APPROACH - Julia Nurul Alifah (PT. Samudra Solusi Profesional, 2025)
The growth of Islamic banking in Indonesia has not been accompanied by proportional adoption among non-Muslim consumers, despite increasing awareness and regulatory support. This study aims to examine the affective and cognitive factors influencing non-Muslim consumers’ behavioral intention to useIslamic banking services in Indonesia by employing an extended Theory of Planned Behavior (TPB). Specifically, this study investigates the role of knowledge as an antecedent of attitude, subjective norm, and perceived behavioral control, and their subsequent effects on behavioral intention. This research adopts a quantitative explanatory approach using primary data collected through an online questionnaire. The sample consists of 220 nonMuslim respondents in Indonesia who are aware of Islamic banking but have not become active customers. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Measurement items were adapted from Mustapha et al. (2022) and assessed for reliability and validity through convergent validity, discriminant validity, and internal consistency tests.The results indicate that all proposed hypotheses are supported. Knowledge has a strong and significant positive effect on attitude, subjective norm, and perceived behavioral control. Furthermore, attitude, subjective norm, and perceived behavioral control significantly influence behavioral intention, with attitude emerging as the strongest predictor. The model demonstrates substantialexplanatory power, explaining 63.2% of the variance in behavioral intention. These findings suggest that non-Muslim consumers’ intention to use Islamic banking services is primarily driven by cognitive understanding, evaluative judgment, social influence, and perceived capability, rather than religious considerations.This study contributes to the literature by extending the TPB framework and providing empirical evidence from a non-Muslim context in a pluralistic society. Practically, the findings imply that Islamic banks should emphasize knowledge dissemination, ethical value communication, and service accessibility to attract non-Muslim consumers and promote inclusive financial development in Indonesia.